Profesionalisme Kerja Pegawai pada Kantor Dinas Kependudukan dan Pencatatan Sipil Kota Ambon - Maryam Salampessy; Matheus Rumaratu (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2021)
This study aims to determine the quality of public services at the Ambon City’s Population and Civil Registration Service Offices, and the dimensions of employee professionalism which are supporting and inhibiting factors for improving the quality of public services at the Ambon City’s Population and Civil Registration Service Offices. The data was collected in this study were analyzed using descriptive qualitative analysis techniques through steps, or components of interactive model data analysis. Data collection techniques used through this research are interviews, observation and documentation. The results of this study indicate, the level of quality of public services by the administering apparatus of the field of population administration and civil registration at the Ambon City’s Population and Civil Registration Service is in sufficient condition, this is a contribution of the employee's work professionalism factor.